Agro-industry business in Colombia : An analysis of power relations and configuration of the ownership of productive factors - Valencia Toro, Marcela (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2016)
Agroindustrial organizations have become one of the most important productive bets for Latin American countries. This article begins with a question: Has the Colombian government developed legal tools regarding fundamental productive factors (land and labor) to enable increased profits for agribusinesses? To answer this question, a conceptual framework is established on the basis of the relational conception of power. Furthermore, a concept of land ownership in Latin America is presented from a historical perspective, culminating in the characterization of agribusiness in the country. The general framework of the analysis is the impact and influence of the Colombian conflict on land ownership.